Financial Institutions, Financial Contagion, and Financial Crises - Huang, Haizhou; Xu, Chenggang (Washington, D.C. : International Monetary Fund, 2000)
Financial crises are endogenized through corporate and interbank market institutions. Single-bank financing leads to a pooling equilibrium in the interbank market. With private information about one's own solvency, the best illiquid banks will not borrow but rather will liquidate some premature assets. The withdrawals of the best banks from the interbank market may lead more solvent but illiquid banks to withdraw from the market, until the interbank market collapses. However, multi-bank financing leads to a separating equilibrium in the interbank market. Thus, bank runs are limited to illiquid and insolvent banks, and idiosyncratic shocks never trigger a contagious bank run.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet